UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUIMODEL PEMBELAJARANKOOPERATIF TIPE JIGSAW PADA PEMBELAJARAN PKN DI KELAS lll SDN 14 BENGKAYANG - Rani Sulistiani (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research aims to determine efforts to improve student learning outcomes through the jigsaw type cooperative learning model in Civics learning in class III at SDN 14 Bengkayang. This research uses a classroom action research (PTK) approach which aims to improve student learning outcomes. The data analysis technique used isquantitative data using the Excel program. The data collection technique used is a testin the form of multiple choice questions and observation. Based on the results of this research, learning using the jigsaw type cooperative learning model improves studentlearning outcomes in class III at SDN 14 Bengkayang.